(untitled) (Journal of the College of Basic Education, 2026)
Islamic education is considered one of the important foundations for building an Islamic society. It works to develop the individual Muslim personality in an effective and positive manner. It relies primarily on the ethical and behavioral concepts and values, as well as the purposeful education provided by the Holy Qur’an and the Sunnah. It reinforces a Muslim’s sense of belonging to his religion and his homeland, and strengthens his awareness of Islamic heritage and its moral and social obligations, which align with the needs of society and do not conflict with the fundamental principles of Islamic law. Islamic education, whose foundations are based on the provisions of the Qur’an and the Sunnah, works to achieve integration between the spiritual and intellectual aspects in a comprehensive manner that encompasses the spiritual, cognitive, moral, and behavioral aspects of the Muslim personality in a balanced and disciplined manner. In all of this, it is consistent with the human nature with which God created people, and does not contradict or deviate from it. Rather, it is compatible and harmonious in a way that preserves human dignity and pride, preserves identity, develops character, and achieves the desired worldly and eternal happiness, which is the aspiration and goal of every human being in this life.